Impact of shift work on a woman's body - Syrocka, Joanna; Gaworska-Krzemińska, Aleksandra; Barton, Marzena (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. It is obvious that nurse’s work is expose to many harmful factors. Next to biological, physical and chemical factors more often researchers’ attention is directed to health effects of shift work especially work at night. This system of work causes disruption of difference between day and night moreover, there is a disturbance of melatonin secrete which protect against cancer. Long shift work can cause: cancer, menses disorder, problems with becoming pregnant, lower baby’s weight or lack of sexual gratification. Aim. Get to know how shift work influence on selected areas of functioning of woman health. Material and methods. Research was taken place at the Clinic University Centre and at the Centre of Invasive Medicine in Gdansk among 152 nurses in 2014. In this paper the diagnostic survey and autorship questionaire were used. The questionaire was based on published literature in the field of thematic research. Statistical analysis was drew on the R statistical software, version 3,0,2 and Excel spreadsheet. Results. Statistically significant connection was received between the number of night shifts per month and occur nodules in the breast (p = 0.019). Studies have shown that significantly more nodules in the breast appeared in nurses with 4–6 night shifts per month, than in those who had 0–3 night shifts. Conclusions. Quantitative analysis conducted research showed negative change of nurse’s health after they have taken shift work. However difference between nurses working 12 hours a day with night shift and those working during daytime was not proved explicitly. It is crucial that more research into influence shift work on nurse’s health should be taken place on larger population.